AB0768 Clinical features of rheumatoid factor- or anti-cyclic citrullinated peptides-positive patients with psoriatic arthritis. (15th June 2017) - Inui, K; Okano, T; Yoshimura, H; Sugioka, Y; Mamoto, K; Koike, T; Tada, M; Nakamura, H
Abstract : Background: Although rheumatoid factor (RF) negativity is among the Classification Criteria for Psoriatic Arthritis (CASPAR) for the diagnosis of psoriatic arthritis (PsA), not all patients with PsA are seronegative. Measurement of anti-cyclic citrullinated peptides (ACPA) is another key test for rheumatoid arthritis and PsA; however, the prevalence of ACPA in patients with PsA is unclear. Objectives: We analyzed the clinical features of RF- or ACPA-seropositive patients with PsA in comparison with seronegative patients with PsA using the ISLAND registry (UMIN000024292). Methods: One hundred patients with psoriasis referred from dermatologists for assessment of synovitis or enthesitis from July 2015 to August 2016 were enrolled. PsA was diagnosed by CASPAR, and synovitis or enthesitis was confirmed by ultrasound assessment. Factors compared between seropositive and seronegative patients included age, sex, comorbidities, use of disease-modifying antirheumatic drugs, prevalence of enthesopathy, eye symptoms, duration between skin onset and musculoskeletal onset, psoriasis area severity index, composite psoriatic disease activity (CPDAI), psoriatic arthritis screening and evaluation (PASE), disease activity score-28 (DAS-28), and laboratory data. Results: In total, 52 patients had PsA and 48 patients had psoriasis without any musculoskeletal manifestations. Significant differences were observed in the age at onset of psoriasis (37.4 vs. 47.9 y, respectively; p<0.01) and several clinical parameters (CPDAI: 14.60 vs. 4.55, respectively [p <0.01], PASE: 50.8 vs. 32.0, respectively [p <0.01], DAS-28: 3.77 vs. 2.72, respectively [p =0.009]). ACPA positivity was observed in 15.9% of patients with PsA and in 0.0% of patients with psoriasis (p=0.04). Among 44 of the 52 patients with PsA whose ACPA data were available, the duration from skin onset to joint onset was shorter in the 7 ACPA-positive patients (54.3±52.8 months) than in the 37 ACPA-negative patients (147.8±158.0 months), although the difference was not statistically significant (p=0.30). There were no statistically significant differences in the PASE, DAS-28, C-reactive protein concentration, or matrix metalloproteinase-3 concentration. The differences between RF positive and negative patients were not also statistically significant. Conclusions: Among the patients with PsA in this series, ACPA positivity occurred in 15.9% and RF positivity occurred in 12.8%. Seropositive patients with PsA tended to have a shorter duration between skin onset and joint onset. Clinical and laboratory findings were not significantly different between ACPA-positive and -negative patients. One possible explanation for this is that 40.4% of patients with PsA received biological disease-modifying antirheumatic drugs; therefore, their disease activity was stable. Disclosure of Interest: None declared